Evaluasi potensi genetik galur murni boer (Faculty of Animal Science, Universitas Brawijaya, 2011)
Abstract : Study on genetic potency of pure line Boer was conducted at station research of Sumber Sekar, Faculty of Animal Husbandry, Brawijaya University, Malang, Indonesia. A number of 85 offspring resulted from crossing between dam of Local and sire of 6 (six) blood lines of Boer goat were used in the study. Data were analysed using the analysis of variance procedure with REML (Restricted Maximum Likelihood) method using mixed procedure of SAS. The overall mean of birth weight of offspring crossbred Boer - Local was 3.10 kg ± 0.73 kg. There was no significant difference in birth weight of offspring between blood lines and also between sire within the blood lines. Analysis of variance showed that the average of birth weight was highly significant (P<0.01) affected by type of birth and sex determination of the offspring. The mean values for single, twins and triplets kids were 3.26 ± 0.33 3.20 ± 0.75 and 2.51 ± 0.64, respectively. Type of birth tended to be twins (70.24%) and the rest were for single (15.48%) and triplets (14.29%). Estimation of variance components were 0,052 and 0,406 for blood line and error variance, respectively. Heritability value was moderate, which was 0,4541. Key words: Boer goat, Local Goat, Birth weight, Type of birth, Heritability.